Pemberdayaan Masyarakat BerbasisBadan Usaha Milik Desa (Bumdesa) Di Desa Kendalbulur Kecamatan Boyolangu Kabupaten Tulungagung - Yuniarko, Wahyu; Pramono, Teguh (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
This research was conducted with the aim of 1) describing and analyzing community empowerment through BUMDesa Larasati 2) describing and analyzing what are the factors that hinder and support community empowerment through BUMDesa Larasati. This research is a qualitative research, with a descriptive approach. The informants in this study are the Director, Manager of the Online Payment Business Unit, Treasurer, BumDesa Supervisory Member, MSME business owner and Warung business owner. The data collection techniques used in this research are observation, interviews, and documentation. Meanwhile, data analysis techniques include data condensation, data presentation, and drawing conclusions. The results of this study show that Community Empowerment through BUMDesa Larasati runs optimally in empowering the community. The empowerment stage carried out consists of an awareness stage where the community that is the subject of empowerment is given an awareness that every human being has potential that can continue to be developed. The next stage is the capacity stage, this process can be achieved if the community already has the ability to receive power; and finally the stage of empowerment where the community is empowered, authority, or opportunity to develop to achieve independence. Supporting factors in community empowerment are the potential to be developed and a culture of mutual cooperation and community togetherness that is quite close. The inhibiting factor is that community involvement in the BUMDesa Larasati unit is less than optimal due to inadequate human resources.